Isolation and Characterization of Canine Factor IX - Sugahara, Yuichi; Catalfamo, James; Brooks, Marjory; Hitomi, Eri; Bajaj, S Paul; Kurachi, Kotoku (Thrombosis and Haemostasis, 1996)
Canine plasma factor IX was purified to homogeneity by a combination of barium citrate precipitation and three-step column chromatographies of DEAE sepharose, heparin agarose and a monoclonal antifactor IX antibody-linked agarose. Canine factor IX has an apparent molecular size of 61 kDa, which is slightly smaller than that of human factor IX, as determined by denatured polyacrylamide gel electrophoresis. Its amino acid composition, amino-terminal and carboxyterminal amino acid sequences agreed well with those predicted from the reported cDNA. Unlike purified human factor IX, canine factor IX preparation often showed a discrete smaller molecular species (∼50 kDa) which was generated by a specific proteolytic cleavage between Arg310 and Val311. When purified canine factor IX was utilized as a standard for enzyme linked immunosorbent assay, the concentration of canine factor IX in the pooled normal dog plasma was determined to be 5.3 Μg/ml with 11.2% carbohydrate content (or 4.7 Μg/ml for its polypeptide chain moiety). Concentration of plasma factor IX antigen was measured in six severely affected, unrelated hemophilia B dogs. Four had factor IX antigen of less than 1% of the normal, and two had undetectable levels. The latter two had gross molecular abnormalities in their factor IX genes. Three obligate carrier females had variable but proportionately reduced factor IX antigen and factor IX coagulant activity levels. These results provide a quantitative method for measuring canine factor IX antigen which is a prerequisite for studying hemostasis and development of gene transfer approaches in the canine model of hemophilia B.